2013
DOI: 10.1074/jbc.m113.452177
|View full text |Cite
|
Sign up to set email alerts
|

Multispecificity of Immunoglobulin M Antibodies Raised against Advanced Glycation End Products

Abstract: Background: Advanced glycation end products (AGEs) can act as neoantigens to trigger immune responses. Results: Natural IgM antibodies against AGEs recognize multiple molecules, including DNA and chemically modified proteins. Conclusion: There is a close relationship between the formation of AGEs and innate immune responses. Significance: Our findings highlight AGEs and related modified proteins as a source of multispecific natural antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…IgM NA are often positively charged to facilitate interaction with negatively charged targets (53), and may have high levels of poly-reactivity (54). Murine B1 cells secreting NA are also TLR-responsive (11, 55) and have unique BCR construction (56), making them distinct from pathogenic antinuclear autoantibody producing cells (57).…”
Section: Discussionmentioning
confidence: 99%
“…IgM NA are often positively charged to facilitate interaction with negatively charged targets (53), and may have high levels of poly-reactivity (54). Murine B1 cells secreting NA are also TLR-responsive (11, 55) and have unique BCR construction (56), making them distinct from pathogenic antinuclear autoantibody producing cells (57).…”
Section: Discussionmentioning
confidence: 99%
“…Miho Chikazawa suggested that the AGEs could be an endogenous source of innate epitopes recognized by natural IgM antibodies patients with systemic lupus erythematosus with significantly higher serum levels of the IgM titer against the AGEs when compared to the healthy individuals. It was suggested that the protein modification by the endogenous carbonyl compounds generates electronegative proteins that induce multi specific natural antibodies [64].…”
Section: Role Of Glyoxidation Modified Histones In Autoimmune Diseasesmentioning
confidence: 99%
“…Cell images were recorded as described above. The anti-AGE mouse IgM (ab18400, Abcam), the same isotype with E06 mAb, served as a negative control (41). To inactivate E06 mAb, 20 g/ml phosphorylcholine salt (Fisher) was pre-mixed with antibody in L-15 medium before incubating with the cells.…”
Section: Methodsmentioning
confidence: 99%
“…Because phosphatidylcholine is a major component of the outer leaflet of the plasma membrane, it seemed reasonable that this antibody might be sufficient to display an effect (52). Cells were pretreated with E06 mAb (50 g/ml) or a control IgM monoclonal antibody not targeting oxidized lipids (its epitope are advanced glycation end products) (41). The phosphorylcholine salt (PC salt) was also optionally added to media, as this molecule inhibits the binding of E06 mAb to the polar head of Ox-PC (53).…”
Section: Identification Of Efficient Cpps and Robustmentioning
confidence: 99%